Diagnosis of the tax behavior of merchants in the city of Ocaña - Ibañez Rueda, Carmen Amanda (Universidad Francisco de Paula Santander, 2014)
Taking into account the investigations proposed by the Area of research of the Center for research development and development business (CIDFE) attached to the Faculty of Administrative Sciences and Economics (FCAE) of the Universidad Francisco de Paula Santander Ocaña (UFPSO), will be a diagnostic tax behavior of merchants of the city of Ocaña, Norte de Santander, in order to identify all those traders who do not pay taxes, or that are unaware of compulsory that they have these in the fulfillment of the payment of taxes. Also research seeks to identify the training needs of merchants of the city of Ocaña have with regard to the tax laws of our country. At the same time, to comply with the objectives proposed in this research, it will be known on methodological aspects, using techniques and research tools that measure the amount of merchants of the city of Ocaña that are unaware of the payment of taxes or to evade this obligation.